The Motion of Body Center of Mass During Walking: A Review Oriented to Clinical Applications - Tesio, Luigi; Rota, Viviana (Frontiers in Neurology, 2019)
Human walking is usually conceived as the cyclic rotation of the limbs. The goal of lower-limb movements, however, is the forward translation of the body system, which can be mechanically represented by its center of mass (CoM). Lower limbs act as struts of an inverted pendulum, allowing minimization of muscle work, from infancy to old age. The plantar flexors of the trailing limbs have been identified as the main engines of CoM propulsion. Motion of the CoM can be investigated through refined techniques, but research has been focused on the fields of human and animal physiology rather than clinical medicine. Alterations in CoM motion could reveal motor impairments that are not detectable by clinical observation. In asymmetric gaits, the affected lower limb avoids muscle work by oscillating almost passively, but extra work is required from the unaffected side during the next step. Generally, the average work across a stride remains normal. In more demanding conditions (such as walking faster or uphill), the affected limb can actually provide more work; however, the unaffected limb does also, and asymmetry between the steps persists. This “learned” or “acquired” asymmetry is a formerly unsuspected challenge to rehabilitation attempts to restore symmetry. Techniques of selective loading of the affected side, which include constraining the motion of the unaffected limb or forcing the use of the affected limb on split-belt treadmills which impose a different velocity and power to either limb, are now under scrutiny. The study of the three-dimensional trajectory of the CoM motion also represents a clinical frontier. After adjusting for displacement due to the average forward speed, the trajectory assumes an figure-of-eight shape (dubbed the “bow-tie”) with a perimeter about 18 cm long. Its lateral size decreases with walking velocity, thus ensuring dynamic stability. Lateral redirection appears as a critical phase of the step, requiring precise muscle sequencing. The shape and size of the “bow-tie” as functions of dynamically equivalent velocities do not change from child to adulthood, despite anatomical growth. The trajectory of the CoM thus appears to be a promising summary index of both balance and the neural maturation of walking